Potential health benefits of integrated screening strategies for alcohol, tobacco, other substance use, depression, anxiety, and chronic pain among people living with HIV in the USA: a mathematical modelling study. Issue 2 (February 2023) - Bershteyn, Anna; Richard, Emma; Zhou, Qinlian; Khan, Maria R; Scheidell, Joy D; Manandhar-Sasaki, Prima; Ban, Kaoon; Crystal, Stephen; Gordon, Adam J; Justice, Amy C; Bryant, Kendall J; Braithwaite, R Scott
Summary: Background: Alcohol use, tobacco use, and other substance use often co-occur with depression, anxiety, and chronic pain, forming a constellation of alcohol, substance, and mood-related (CASM) conditions that disproportionately affects people with HIV in the USA. We used a microsimulation model to evaluate how alternative screening strategies accounting for CASM interdependence could affect life expectancy in people with HIV in the USA. Methods: We augmented a microsimulation model previously validated to predict US adult life expectancy, including in people with HIV. Using data from the Veterans Aging Cohort Study, we incorporated CASM co-occurrence, inferred causal relationships between CASM conditions, and assessed the effects of CASM on HIV treatment and preventive care. We simulated an in-care HIV cohort exposed to alternative CASM screening and diagnostic assessment strategies, ranging from currently recommended screenings (alcohol, tobacco, and depression, with diagnostic assessments for conditions screening positive) to a series of integrated strategies (screening for alcohol, tobacco, or depression with additional diagnostic assessments if any screened positive) to a maximal saturation strategy (diagnostic assessments for all CASM conditions). Findings: The saturation strategy increased life expectancy by 0·95 years (95% CI 0·93–0·98) compared with no screening. Recommended screenings provided much less benefit: 0·06 years (0·03–0·09) gained from alcohol screening, 0·08 years (0·06–0·11) from tobacco screening, 0·10 years (0·08–0·11) from depression screening, and 0·25 years (0·22–0·27) from all three screenings together. One integrated strategy (screening alcohol, tobacco, and depression with diagnostic assessment for all CASM conditions if any screened positive) produced near-maximal benefit (0·82 years [0·80–0·84]) without adding substantial screening burden, albeit requiring additional diagnostic assessments. Interpretation: Primary care providers for people with HIV should consider comprehensive diagnostic assessment of CASM conditions if one or more conditions screen positive. Funding: US National Institute on Alcohol Abuse and Alcoholism.